Diagnostic thoracic imaging - Miller, Wallace T. (McGraw-Hill Medical Pub. Division, 2006)
This well-illustrated resource utilizes a highly-practical pattern-recognition approach to detect and diagnose disease affecting the thoracic compartment. For radiologists, this unique approach which is not found in any other text, provides the clearest and most concise guidelines available for attaining a diagnosis of the full-spectrum of diseases of the thoracic area.